Parameter Pengembangan Produk-Produk Perbankan Syariah Dengan Pendekatan Maqasid Syariah (Studi Kasus di Perbankan Syariah Kabupaten Ponorogo) - Ahmad Muqorobin; Eko Nur Cahyo (Islamic Economics Journal, 2019)
Currently, the development and growth of Islamic banking show a positive trend that increases every year. This encourages Islamic banks to produce innovative products which customer needs. However, the methods used to develop products differ from one country and another. For Indonesia, one parameter is needed to harmonize all product developments produced by Indonesian Islamic banking. The purpose of this study is to explore the challenges of current Islamic banking in producing products and make a parameter as a reference for developing Islamic banking products with the Maqāsid Sharia approach for the realization of maslahah. To achieve this study using several methods such as interviews, content and descriptive analysis. The results of this study are the parameters that have been applied with the development product in Islamic banking Ponorogo citywith the Maqāsid Sharia approach. A product can produce maslahah if the five elements in Maqāsid shari’a are achieved, namely; (1) Preservation of religion by the basis of the product offered is based on the Al-Qur'an, Sunnah, and DSN-MUI, (2) Preservation of life, it is manifested by the service and supply to customers in accordance with Islamic ethics, (3) Preservation of intellect, with a form of banking business to explain in detail related to products offered to customers in a clear, (4) Preservation of wealth, it is realized with the management of property management client in Islam, (5) Preservation of progeny, by applying the four things previously, to guarantee halal and affect the sustainability of living for the family and the children of clients.